Improving Senior High School Students’ Speaking Competence through Retelling YouTube News Videos via Audiovisual Instruction - Sari, Rubiana; Yulia Arfanti; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
Speaking ability is one of the important language skills for students in communicating. However, based on initial observations, many students of class XI SMA Negeri 1 Rantau Utara have difficulty in conveying ideas verbally, especially in retelling the contents of the news they watch. This is due to limited vocabulary, lack of understanding of news structure, and low self-confidence in speaking. Therefore, this study aims to determine the effectiveness of audiovisual learning methods in improving students' speaking competence. This study used an experimental method with a one group pretest-posttest design. The research sample consisted of 32 students selected by purposive sampling. The research instrument was a speaking test, which was conducted before and after treatment. Data were analyzed using a t-test to determine the significance of improving students' speaking competence. The results showed that before treatment, the average pretest score of students was 53.28 with a standard deviation of 8. After being given treatment in the form of learning with news broadcasts from YouTube channels, the average posttest score increased to 83.71 with a standard deviation of 5. The results of the t-test showed that t count (3.36) was greater than t table (2.03) at a significance level of 5%, which means that there was a significant increase in students' speaking ability. This increase indicates that the audiovisual learning method is effective in helping students understand the structure of news, improve their speaking fluency, and enrich their vocabulary. In addition, audiovisual media also increases student involvement in learning and fosters confidence in speaking. Thus, it is suggested that this method be applied in Indonesian language learning to improve students' speaking skills more optimally